La scena platonica di Anatolij Vasil’ev: Giocare tra le idee - Piergiacomi, Enrico (Mimesis Journal, 2020)
This essay reconstructs the reception of Plato’s dialogues in the theatrical practice of the Russian director/pedagogue Anatolij Vasil’ev. It will be argued that the former texts represent a fundamental step forward in the development of the philosophy of theatre of the latter. Vasil’ev recovers from Plato his main perspectives on the performance. More precisely, he considers Platonic dialogues as a preparation to an original method: the “ludic theatre”, i.e. an extemporaneous and playful creation that evokes on the scene some mysterious ideas. The paper concentrates then on the reception of Plato’s Meno and Ion, two dialogues that Vasil’ev studied in depth, as well as on some ethical implications of the philosophy of theatre of Vasil’ev.